THE EFFICIENCY OF TECHNOLOGY TRANSFER – THEORETICAL AND METHODOLOGICAL APPROACH - Andreea-Clara MUNTEANU (Revista Romana de Economie, 2006)
As the importance and complexity level of technological transfer increased, the need of adequate systems of assessing the efficiency of this process became the more obvious. Introducing sustainability criteria requires the creation of a complex framework for analysing and studying efficiency that would incorporate all other three dimensions of contemporary economic development: economic, social and environmental.